(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This piece of research tends to acknowledge the degree of sufficiency that environment and material needs of the students of education at the Facutly of Education are met. It adopts the analytical and descriptive method. Thus, a special questionnaire including (66) points distributed over many significant fields: public location of the building, public safety, public health, public services, pollution, academic spaces and specialist environment to each student, special lecturehalls and seats, projectors and library—has been prepared and targeted a selected specimen of students. This questionnaire has been targeted a randomly selected specimen that included 150 students (fe/males) divided between the two divisions: the educational (Classromm Tutor and Methods), and the psychological (Pschological Monitoring), with special reference to variants of gender and teaching unit. This study concludes with the fact that the extent of meeting the environmental and material expectations of the students of Faculty of Eduation, University of Tishreen has been medium; there exist no statistical differences among the respionses of the specimen students with reference to the variants of gender and teaching unit. In the light of the findings, it seems that the material environment plays a key role in formulating the personality of students, and shaping their future. Undoubtedly, this is so important since it stands as one basic input in the teaching process, and contributes to providing knowledge to mankind, and investing in man as human capital who participates in progessing and improving society, and having an acess to the welfare of human being. Henceforward, with the progess of the theories of education, it is so essential to adapt the academic career to the latest teaching requirements, and the modern eduation tendencies including various activities, improving the teacher-students relationship and opening channels with the outer world.